Nazis among the Cedars: The Inability of the German American Bund to Find Acceptance in Pre-War Milwaukee - Petrie, Stephen L. R. (My University, 2015)
Tracing its roots back through the Friends of New Germany, the German American Bund was founded in 1936 with the express purpose of fomenting a National Socialistic revolution in the United States. The Bund had chapters formed throughout the United States, including in Milwaukee, Wisconsin where they set up Camp Hindenburg, a summer camp for youths located in nearby Grafton. Despite claims of being loyal Americans, the national Bund found itself surrounded by opposition due to public opinion, coordinated attacks, and portrayals in the media. These and other issues lead to the collapse of the Bund with the outbreak of World War II.
Keywords: Nazis--Wisconsin--Milwaukee; German American Bund--History